Valoración del incremento de proteína del amaranto alegría (amaranthus caudatus l.) en el proceso de Germinación. - Guerrero Tipantuña, Carlos Napoleón (2018)
A research was conducted in order to promote the production of amaranth seeds joy (Amaranthus caudatus L.) through the process of germination in order to evaluate the increase of protein to improve the utilization that be supplied like source of protein in the human feeding. During the germination of the seeds of amaranth, it occurred different changes in its composition due to the use of reserves (carbohydrates, lipids and proteins) for the development of its embryonic axis, also, it followed up in the different stages of the germinative process (24, 48 and 72 hours) and germination methods (controlled ºT and uncontrolled ºT) to obtain germinated joy amaranth flour samples, which were evaluated for the determination of protein percentage in the laboratories of the INIAP Santa Catalina station. The best treatments were statistically determined using an experimental design of (axb) +1 where the study factors were: method (20º C germination, 18-24º C greenhouse) and time (24-48-72 hours) of germination and the response variable : protein, it applied the Tukey test at 5% in order to determine significance between treatments (germinated joy amaranth flour) and witness (amaranth flour without germinated), giving as best result the treatment t3(a1b3), at a temperature of 20ºC and a time of 72 hours of germination presenting a protein percentage of 14.53%. The study variables were: % protein (for all treatments), proximal and microbiological analysis (for the best treatments).